2018
DOI: 10.1186/s12940-018-0399-5
|View full text |Cite
|
Sign up to set email alerts
|

Trimester-specific phthalate concentrations and glucose levels among women from a fertility clinic

Abstract: BackgroundSubfertile women are at increased risk of glucose intolerance in pregnancy. Based on epidemiologic studies, exposure to certain phthalates is associated with diabetes, elevated glucose, and increased insulin resistance.ObjectivesTo evaluate the association between urinary phthalate metabolites and pregnancy glucose levels in women seeking medically assisted reproduction.MethodsWe evaluated 245 women participating in a prospective cohort study based at a large fertility clinic who delivered live birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Investigation of environmental exposures on maternal cardiometabolic risk development is another future investigation: increasingly, evidence shows that exposure to metabolism disrupting environmental chemicals such as phthalates and per‐ and polyfluoroalkyl substances (PFAS), can dysregulate the body's ability to adapt to the demands of pregnancy (Borghese et al, 2020; James‐Todd et al, 2018; Varshavsky et al, 2019). Furthermore, elevated concentrations of certain phthalate metabolites and PFAS are associated with adverse cardiometabolic outcomes including excessive gestational weight gain (Bellavia et al, 2017), gestational diabetes mellitus (Zhang et al, 2015), and impaired glucose tolerance (James‐Todd et al, 2018). In postpartum readjustment to the nonpregnant state may be a second critical period of heightened vulnerability to endocrine disruption…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of environmental exposures on maternal cardiometabolic risk development is another future investigation: increasingly, evidence shows that exposure to metabolism disrupting environmental chemicals such as phthalates and per‐ and polyfluoroalkyl substances (PFAS), can dysregulate the body's ability to adapt to the demands of pregnancy (Borghese et al, 2020; James‐Todd et al, 2018; Varshavsky et al, 2019). Furthermore, elevated concentrations of certain phthalate metabolites and PFAS are associated with adverse cardiometabolic outcomes including excessive gestational weight gain (Bellavia et al, 2017), gestational diabetes mellitus (Zhang et al, 2015), and impaired glucose tolerance (James‐Todd et al, 2018). In postpartum readjustment to the nonpregnant state may be a second critical period of heightened vulnerability to endocrine disruption…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between phthalate metabolite concentrations and diabetes in non-pregnant populations [ 45 , 46 ], finding associations between certain phthalate metabolites and diabetes. Few studies have evaluated the role of phthalates on GDM, and they found some associations between different gestation period exposures to phthalates and impaired glucose tolerance [ 47 ]. As far as we know, we are the first study that is trying to look into the association between in-utero exposure to phthalates and GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Serum POPs concentrations were found to be positively associated with GDM risk [9]. In addition, previous studies conducted among pregnant women from the EARTH Study showed that urinary bisphenol A was positively associated with glucose levels [10], urinary butylparaben was positively while propylparaben inversely associated with glucose levels [11], and urinary phthalates also showed associations with glucose levels in mixed directions where a positive association was seen between monoethyl phthalate and glucose but an inverse association was seen between mono-isobutyl phthalate and glucose [12]. The association between BP-3 concentrations and pregnancy glucose levels, however, remains unclear.…”
Section: Discussionmentioning
confidence: 84%
“…For example, persistent organic pollutants (POPs) were found to increase GDM risk in average-risk populations [9]. In addition, we previously found associations between pregnancy glucose levels and certain non-persistent chemicals, including bisphenol A [10], certain parabens [11], and certain phthalates [12], in higher-risk (i.e. subfertile) populations from the same study cohort.…”
Section: Introductionmentioning
confidence: 95%